Comparative evaluation of efficacy and duration of analgesia of clonidine and dexmedetomidine added to ropivacaine in supraclavicular brachial plexus block in upper extremity surgery - Anamitra Mandal; Sourav Naiya; Swarup Datta; Sarbari Swaika; Swapnadeep Sengupta (Asian Journal of Medical Sciences, 2025)
Background: Supraclavicular brachial plexus block is a popular and widely employed regional nerve block technique for perioperative anesthesia and analgesia for surgery of the upper extremity. Local anesthetics alone for supraclavicular brachial plexus block provide good operative conditions but have a shorter duration of post-operative analgesia. Hence, various drugs as adjuvants were used with local anesthetics in the brachial plexus block to prolong the duration of analgesia and also hasten the onset of sensory and motor block. Aims and Objectives: To compare the onset of sensory block, the onset of motor block, and the duration of analgesia of clonidine and dexmedetomidine added to ropivacaine in supraclavicular brachial plexus block. Materials and Methods: The comparative study was carried out in a tertiary care hospital during 2012–2013 to find out the onset of sensory block, onset of motor block, duration of analgesia, and any adverse effects between two groups given a combination ropivacaine with dexmedetomidine and a combination of ropivacaine with clonidine. A total of 80 patients, 40 in each group were allotted randomly after taking informed consent and satisfying the inclusion and exclusion criteria. The efficacy and duration of analgesia between the two groups were assessed in supraclavicular brachial plexus block in upper extremity surgery. Result: The time of onset of sensory block (7.95±2.029) and the onset of motor block (10.05±2.025) was significantly less, and the time to rescue analgesic was significantly longer (563.25±17.19) in ropivacaine–dexmedetomidine group in compare to ropivacaine–clonidine group. Bradycardia was found to be significantly more in the ropivacaine–dexmedetomidine group. Conclusion: Further studies are needed to determine the safe, optimal dose and effect of neurotoxicity of dexmedetomidine added to local anesthetics for supraclavicular brachial plexus block.